LEADERSHIP BEHAVIORAL DEVELOPMENT OF MILLENNIAL LEADERS AS A CHANGE AGENT IN THE DIGITAL TRANSFORMATION ORGANIZATION - Ardi, Ardi; Meilani, Yohana F. Cahya Palupi (Feedforward: Journal of Human Resource, 2024)
The digital transformation era and Industry 4.0 provide ample opportunities for this generation to thrive with their rapid technological adaptation and openness to new ideas. This research examines millennial leadership behavioral development to enable them to effectively become change agents in digital organizations, using the case study of William Tanuwijaya at Tokopedia. Through a review of literature from international sources during 2020-2023, this study discusses millennial leadership theories and change management, highlighting the urgency and importance of adaptive leadership capable of managing change in the face of digital organizational challenges. The research findings indicate that millennial leadership styles vary according to organizational contexts. Millennials are confronted with change management, where organizational readiness to adapt is critical to success. Adaptive leadership, a key strategy in managing change, is crucial. Through William Tanuwijaya's leadership at Tokopedia, millennial leadership characteristics prioritizing social and environmental issues, sustainability, and the implementation of sustainable values are evident, alongside collaboration with the government to create an inclusive environment and focus on innovation and digital transformation in the economy. Leaders like William Tanuwijaya start by building teams consisting of celebrities or public figures in Indonesia to promote Tokopedia and strengthen the company's image while formulating the company's vision and initiatives, motivating employees, overcoming obstacles such as improving work efficiency, implementing successful minor changes, ensuring smooth change integration, and making change an integral part of the organizational culture and system.